Fenología y producción de aguaymanto (physalis peruviana l.) en función de la fertilización n,p,k, en pampas de SAN JUAN, LAREDO, LA LIBERTAD - Otiniano Ulloa, Willyam Eyder (2013)
To determine the influence of increasing doses of N, P2O and K2O, in the growth and the production of Aguaymanto (Physalisperuviana L.) was carried an experiment in Pampas de San Juan, Laredo, La Libertad. The installation was made on 03.10.2010 nursery and transplanting to the field 01.12.2010, evaluations were made up to 08.06.2011, the day of the last harvest. The experimental design used was DCA, with six treatments and six repetitions. The variables evaluated were days to germination, days to flowering, days to harvest, plant height, number of fruits, fruit weight, yield, soluble solids and pH. The results indicate 22dds for germination, emergence 19ddt for the first floral bud and the 87ddt harvest, for plant height variable the T5 has a linear response in the Evaluations 6, 8 and 11, on the variable number of fruits, the T2 has better results, with excellent results, E7, E8 and E9, for fruit weight variable T2 is the best performer in the evaluations E7, E8 and E9 to significant level in terms Rdto.ha-1, the T2 has better results in the harvest number 07, referring to the soluble solids, the T6 has a higher content 13.9 º Brix, because treatment with the highest dose of K2O. For pH the T6 is the best